Evaluation of subjective well-being: Analysis of the Satisfaction with Life Scale in the Chilean population - Vera Villarroel, Pablo; Universidad de Santiago de Chile (2012)
The aim of this investigation is to evaluate the psychometric properties of the Satisfaction with Life Scale (SWLS), in the adult population from ages 18 to 65. In order to do this two studies were conducted. In the first one, we evaluated the internal consistency and construct validation of data from 330 people between 18 and 52 years of age; in the second study, we evaluated the confirmatory factor and validation of data indicators from 1157 people between 18 and 65 years of age. The results show suitable indicators of internal consistency (Cronbach’s alpha = 0.82), the exploratory and confirmatory factor analysis finds a one factor’s solution. The correlation between the SWLS, the WHOQOL-BREF Quality of Life Questionnaire, and the Difficulties in Emotion Regulation Scale (DERS), display significant, consistent correlations in the expected direction. We conclude that the SWLS is a reliable and valid instrument to use for evaluating the cognitive sphere of subjective well-being in Chile’s adult population